2021
DOI: 10.3389/fpubh.2021.591614
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Ecological Risk and Problem Behaviors Among Adolescents in Secondary Vocational Schools: The Mediating Roles of Core Self-Evaluation and Basic Psychological Need Satisfaction

Abstract: Based on the Cumulative Risk Model, a single risk factor cannot play a decisive role, but the cumulative ecological risks may have complex superposition effects on adolescents' problem behaviors. However, although many studies have investigated the specific influences of single external risk factors on problem behaviors, the effect of cumulative ecological risk on problem behaviors and especially the underlying mechanisms therein have been under-investigated. Therefore, this study aimed to explore the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Although these frameworks may vary, most of them reflect the principles of the social ecological model, a simple but far-reaching framework for public health [ 31 , 32 ]. Based on the research on SERFs, some studies have reported that the high social-ecological risk group of adolescents is at higher risk of psychological, emotional, and behavioral problems [ 23 , 33 ]. Individuals are often faced with multiple risks at the same time, if only focus on a single area is inconsistent with the reality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these frameworks may vary, most of them reflect the principles of the social ecological model, a simple but far-reaching framework for public health [ 31 , 32 ]. Based on the research on SERFs, some studies have reported that the high social-ecological risk group of adolescents is at higher risk of psychological, emotional, and behavioral problems [ 23 , 33 ]. Individuals are often faced with multiple risks at the same time, if only focus on a single area is inconsistent with the reality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes different risk factors do not act independently. More often, multiple risk factors at the same time [ 33 , 34 ]. Our results demonstrated that cumulative SERFs were positively correlated with clustering of HRBs and HRB cooccurrence, consistent with ecological system theory.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high core self-evaluation are full of confidence in life, believe that they have a good sense of control over most things in life, and less anxiety due to lack of control [ 9 ]. Anxiety refers to an unpleasant inner conflict that an individual has in the face of an upcoming event that may pose a threat, accompanied by certain emotional and physical symptoms, such as anger, tension, insomnia, and stomach pain [ 10 ]. Previous studies [ 11 , 12 ] have shown that anxiety can positively predict mobile phone dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Also adolescents feel less connected to the classmates or friends and less popular at school may also be a key determinant of emotional depression (41). The strongest risk factors for adolescent depression are exposure to psychosocial stress and a family history of depression (42). Hence, our study highlighted the magnitudes of risk factors for adolescent depression especially the school and family-related factors that may consistently and closely expose adolescents to a psychologically distressing situation.…”
Section: Discussionmentioning
confidence: 77%